A highly glucose-tolerant GH1 β-glucosidase with greater conversion rate of soybean isoflavones in monogastric animals. (1st June 2018) - Cao, Huifang; Zhang, Yueqi; Shi, Pengjun; Ma, Rui; Yang, Hong; Xia, Wei; Cui, Ying; Luo, Huiying; Bai, Yingguo; Yao, Bin
Abstract: In the feed industry, β-glucosidase has been widely used in the conversion of inactive and bounded soybean isoflavones into active aglycones. However, the conversion is frequently inhibited by the high concentration of intestinal glucose in monogastric animals. In this study, a GH1 β-glucosidase ( As BG1) with high specific activity, thermostability and glucose tolerance (IC 50  = 800 mM) was identified. It showed great glucose tolerance against substrates with hydrophobic aryl ligands (such as p NPG and soy isoflavones). Using soybean meal as the substrate, As BG1 exhibited higher hydrolysis efficiency than the GH3 counterpart Bgl3A with or without the presence of glucose in the reaction system. Furthermore, it is the first time to find that the endogenous β-glucosidase of soybean meal, mostly belonging to GH3, plays a role in the hydrolysis of soybean isoflavones and is highly sensitive to glucose. These findings lead to a conclusion that the GH1 rather than GH3 β-glucosidase has prosperous application advantages in the conversion of soybean isoflavones in the feed industry.